Corporate Criminal Liability As An Insurance Crime Perpetrator Based On Law Number 1 Of 2023 On Criminal Law - Rusli Rusli; Firman Halawa (CV. AFDIFAL MAJU BERKAH, 2024)
The Insurance Law and the Indonesian Penal Code regulate criminal acts such as fraud during agreements and insurance claims. However, prior to Law No. 1 of 2023, criminal liability applied only to individuals, not corporations. This specific law establishes corporate criminal liability in insurance matters, enabling prosecution against corporations and their executives. Cumulative criminal threats are challenging to impose on corporations as they apply to executives, not the corporation itself. This study is a normative legal investigation exploring regulations, principles, and legal norms, aiming to accurately comprehend corporate criminal liability in the insurance field in Indonesia. Insurance crimes in Indonesia before the enactment of Law No. 1 of 2023, such as fraud during agreements and claims, were governed by Articles 381 and 382 of the Penal Code. Insurance Law No. 40 of 2014 covers ten articles encompassing insurance crimes, including operating without a license, document forgery, and misuse of confidential information. Articles 45-50 of Law No. 1 of 2023 establish corporations as subjects of criminal acts in insurance. Penal sanctions include fines and additional penalties, focusing on impact assessment and losses, governing a specific accountability system within insurance-related criminal acts.